DRIVING BUSINESS GROWTH THROUGH DATA-DRIVEN DECISION MAKING: THE ROLE OF MARKETING AUTOMATION - Johanes, Budi
The business game has completely transformed itself as information becomes more abundant and technology continues to advance rapidly. What this means is that there are now many opportunities for data-driven decision making towards company growth. This research, therefore, seeks to evaluate the impact of marketing automation systems on marketing communication channel, with a quantitative analysis approach using data from organizations which implemented these systems. It has become essential for all businesses to use software called Marketing Automation; this is because it helps in automating repetitive marketing tasks. For instance, instead of manually sending emails or advertising to the same customer segment with the same posts, this job can now be automated using marketing automation software, even to the point of personalizing messages based on different segments. This approach increases customer engagement, resulting in higher adoption rates and ultimately accelerating the company's growth rate while significantly impacting profit margins over time. This research will contribute new knowledge by demonstrating the positive effects on organizational growth rates due to the adoption of marketing automation tools. Based on these findings, it can be said that once companies decide to move to an automated platform, their efficiency levels begin to increase dramatically. Findings indicate that businesses using marketing automation platforms for data-driven decision-making have higher effectiveness rates and attract more customers, thus improving the overall performance of the company. Potential challenges during implementation, such as integrating data management systems or customizing processes to address organizational readiness issues, are also mentioned here. By examining the extent to which Marketing Automation supports Business Growth, the insights gained here are relevant both within academic circles and among practitioners seeking sustainable ways to achieve business goals through marketing communication channels. It recognizes the importance of basing marketing strategies on information and highlights areas where marketing automation can bring about sustainable business growth. The results provide practical guidance for organizations that want to optimize their marketing activities by adopting successful strategies that will enable them to achieve a competitive edge over the long term through the use of appropriate marketing automation systems